2018
DOI: 10.1080/20797222.2017.1401304
|View full text |Cite
|
Sign up to set email alerts
|

Stories of Suffering and Success: Men’s Embodied Narratives following Bariatric Surgery

Abstract: This paper draws on research exploring how men narrate their long-term experiences of Weight Loss Surgery [WLS] and is specifically focused on findings relating to male embodiment. Whilst there is concern about increasing obesity and the possible role of bariatric [WLS] surgery in ameliorating this, there has been little research to date exploring men's longer-term experiences of this. For the purposes of the present study, interviews were conducted with five men who had undergone bariatric surgery at least fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Other research has shown profound shifts in people's lived experiences in the years after bariatric surgery, mirroring their bodily transformations [30][31][32][33]. Negative judgments of postbariatric bodies are commonly reported in the literature, often centering on the persistence of side effects from the surgeries [34][35][36][37][38] and/or difficulties with managing the rigid personal habits the surgeries necessitate [32][33][34][35][36][37][38]. Other negative judgments stem from the shapes and sizes of the bodies produced by the surgery and its accompanying rapid weight loss.…”
Section: Plos Onementioning
confidence: 99%
“…Other research has shown profound shifts in people's lived experiences in the years after bariatric surgery, mirroring their bodily transformations [30][31][32][33]. Negative judgments of postbariatric bodies are commonly reported in the literature, often centering on the persistence of side effects from the surgeries [34][35][36][37][38] and/or difficulties with managing the rigid personal habits the surgeries necessitate [32][33][34][35][36][37][38]. Other negative judgments stem from the shapes and sizes of the bodies produced by the surgery and its accompanying rapid weight loss.…”
Section: Plos Onementioning
confidence: 99%
“…Qualitative studies allow us to understand the meanings of this procedure to the candidates [7][8][9][10][11] , to comprehend how these meanings affect the surgery outcomes [12] , and to clarify the expectations, perceptions, and beliefs about obesity surgery among would-be bariatric patients [7,11] . It is important to highlight that "obesity" designates fatness as pathological.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, words such as "high body weight" and "large body" were used [13] . Most bariatric programs-and the research that flows from them-still attempt to understand the lived experiences of bariatric surgery and its attendant weight loss through a focus on the moral individual: Individuals classified with obesity "fail" to make effective lifestyle changes before and even after the surgery, reinforcing the sociocultural view of people with higher body weight as "undisciplined", "without willpower" and responsible for their condition [7][8][9][10][11] . Less is understood about how weight loss and surgery are placed by patients in the context of their specific life trajectories; that is, how they come to understand the broader processes in which their own weight was and remains embedded.…”
Section: Introductionmentioning
confidence: 99%